Supervisi Kepala Sekolah untuk Meningkatkan Kinerja Guru PAI di SD Muhammadiyah Singaraja - Djlantik, Anak Agung Monny Aryadi; Sulthan Syahril; Sigit Hananto (UNISAN JURNAL, 2025)
This study aims to describe the implementation of principal supervision in improving the performance of Islamic Education (PAI) teachers at SD Muhammadiyah Singaraja during the 2024/2025 academic year. The research employed a qualitative approach with a descriptive method. Data were collected through interviews, observations, and documentation, and were analyzed using data reduction, data display, and conclusion drawing. The findings show that principal supervision is carried out through structured planning, implementation, and evaluation of academic supervision. The supervision includes classroom visits, guidance on instructional administration, reflective discussions, and continuous mentoring. The implementation of supervision has a positive impact on enhancing the performance of PAI teachers, as seen in improved lesson planning, teaching methods, classroom management, and assessment practices. Thus, principal supervision plays a strategic role in strengthening the professionalism and performance of Islamic Education teachers in the school.